INFLUENCE ON LEVEL OF LYCOPENE, ANTIOXIDANTS AND OTHER NUTRITIONAL CHANGES ON FORTIFICATION OF LYCOPENE POWDER IN TOMATO SOUP - G. PRATHIBHA; C. K. NARAYANA; T. V. YADAV (The Bioscan, 2015)
In the experiment the tomato soup was fortified with different concentrations (control, 2, 15, 30 mg/100g) of tomato soup was with lycopene powder, extracted from extracted from tomato peel by enzyme mediated method. The fortified soups were stored in pre-sterilized 200ml glass bottles at ambient conditions (26.6-32.3ºC ad 22.6-53.6 % RH) for 60 days and tested for nutritional changes and sensory evaluation. The treatment of lycopene fortified tomato soup at rate of 30 mg/100g had highest antioxidant activity (12.53 mg Ascorbic Acid Equivalence(AAE)/100g) and it increased at 30th and 60th day (18.77 and 23.04mg AAE/100g respectively). Maximum lycopene content (18.17, 17.31 and 15.97 mg/100g), total phenols (23.01, 22.87 and 21.45 mg GAE/ 100g), protein (8.71, 6.27 2.97 mg/100g) and fat content (6.14, 5.91 and 5.05 %) was observed in treatment of lycopene fortified tomato soup at rate of 30 mg/100g at 0th, 30th and 60th day and a decreasing trend was shown in these parameters with advancing storage period.